The Tachytrechus alatus species group (= Syntomoneurum Becker) revisited: new species and revised species group limits (Diptera: Dolichopodidae) - Brooks, Scott E.; Cumming, Jeffrey M. (Zootaxa, 2008)
The Tachytrechus alatus species group is revised. The species group is defined within the genus Tachytrechus on the basis of possession of a strong basiventral bristle on the fore femur and very reduced pulvilli on the midand hindlegs of both sexes. Males also possess a strongly reduced vertical bristle, and a cluster of 2–3 strong bristles on both the fore femur and mid coxa. The T. alatus species group is now known from southern Mexico, Central and South America and comprises eight Neotropical species including three new species: Tachytrechus alatus (Becker), Tachytrechus analis (Parent), Tachytrechus costaricensis Brooks sp. nov., Tachytrechus dios Brooks sp. nov., Tachytrechus giganteus (Brooks), Tachytrechus peruicus Yang & Zhang, Tachytrechus transversus (Van Duzee) and Tachytrechus zumbadoi Brooks sp. nov. A revised key to species is provided, as well as remarks on the phylogeny and zoogeography of the group.